Return of the De Minimis Exception in Digital Music Sampling: The Ninth Circuit's Recent Holding in VMG Salsoul Improves Upon the Sixth Circuit's Holding in Bridgeport, But Raises Questions of its Own - Francesco Di Cosmo (Washington University Law Review, 2017)
Sampling is a musical production practice that has become increasingly common since the 1980s. A producer samples by copying a section of a sound recording and inserting it into the piece of music she is producing. The type of sound recording sampled by producers can vary vastly from piece to piece. Numerous pop and hip hop songs sample from songs of various genres (rock, classical music, or other pop songs, for example). Audio from a film, commercial, or speech may also be inserted into a song. Typically, the purpose of these samples is either to make use of the musical value of the sample or to trigger some sense of familiarity in the listener. Some artists have made a career entirely out of sampling sections of different songs and fusing them into one piece. Often, samples are somehow altered or adapted to make the sound fit within the new piece. This may include altering pitch, key, or speed, and may require the producer to isolate the sample from other sounds that occur simultaneously in the original work. Samples also tend to be short segments of the original work, no more than a few seconds long. However, while these are the trends in sampling, they are not the rule. Predictably, sampling creates a copyright issue when the sampled piece is under copyright and the sampling producer does not acquire a license to use the sampled copyrighted material. In a number of copyright contexts outside of music sampling, courts have found that there exists a de minimis exception to copyright infringement. This exception provides that even where copyrighted material is used without a license, in cases where the use was particularly brief or otherwise insubstantial, the unlicensed use will not constitute copyright infringement, even if all other elements of copyright infringement are met. Within the context of the music industry, a circuit split has emerged with respect to the recognition of the de minimis exception. Specifically, the split revolves around recognition of the exception where a producer of a musical work samples a copyrighted digital sound recording without license to do so. In 2005, the Sixth Circuit held in Bridgeport Music, Inc. v. Dimension Films that the de minimis exception does not exist in the context of digital sound sampling. Therefore, the court held, all unlicensed sampling of copyrighted digital sound recordings is completely prohibited, no matter how short or minimal the sample. Eleven years later, in 2016, the Ninth Circuit reached the opposite conclusion, holding that a de minimis exception does exist in the context of digital sound sampling. Therefore, unlicensed sampling of copyrighted digital sound recordings does not constitute copyright infringement if the average audience would not recognize the appropriation. While the Ninth Circuit’s opinion is persuasive in its legal analysis, which focuses heavily on congressional intent, the average audience test for de minimis use that follows from its ruling creates certain significant problems that do not exist under the Sixth Circuit’s bright-line rule prohibiting all unlicensed sampling. Parts I, II, and III of this note will explain the differences between the Sixth Circuit’s reasoning in Bridgeport and the Ninth Circuit’s reasoning in VMG Salsoul. While the focus of these parts is on illustrating the flaws in the Sixth Circuit’s legal analysis, it will also introduce the complications that arise from the Ninth Circuit’s average audience test, which do not exist under the Sixth Circuit’s simpler, bright-line rule. Part IV will introduce scholarly criticism of another test used in copyright contexts—the substantial similarity test—and examine the ways in which the average audience test announced by the Ninth Circuit in VMG Salsoul shares the same flaws for which the substantial similarity test has been criticized. Finally, Part V will examine proposals for improving upon the average audience test.
Keywords: digital sampling; music sampling; copyright; de minimis exception; VMG Salsoul; LLC v. Ciccone; 824 F.3d 871 (9th Cir. 2016); Bridgeport Music; Inc. v. Dimension Films; 410 F.3d 792 (6th Cir. 2005)